Wprowadzenie do problematyki zarządzania personelem - Borys, Tadeusz (Introduction to Personnel Management, 2008)
The article confronts many approaches towards the research subject of personnel management in the context of relations between the following key notions: management, system, management system and personnel. The importance of the role and style of personnel management function in an organization was presented in relation to an individual's life quality in his/her professional function as an employee. The usefulness of, accepted in the article, division into technocratic and humanistic/empathic personnel management was substantiated. The second approach is observed as one of the biggest challenges, not only at the level of personnel management, but also at the level of global civilization challenge. The final part of the study takes up an attempt of the problem of interdisciplinary identification with regard to the domain: personnel management. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 15-22